Akulturasi Antara Budaya Wisatawan Dan Masyarakat Lokal Dalam Kepariwisataan Bali - Budarma, I Ketut (Jurnal Ilmiah Pariwisata, 2012)
Bali has been developed as a tourist destination since 1920s, initiated by the Dutch Colonial, and then developed as a mass tourism since the opening of Ngurah Rai International Airport in 1968. Tourism in Bali is cultural tourism, exposing Balinese culture as the main product. Long interaction between Balinese and tourists has resulted in acculturation, making Balinese live in two worlds, traditional world and touristic world. Both worlds are interdependent but sometimes there is a conflict of interests between the two. Seeing the phenomenon a research is done focusing on acculturation between tourists’ and local culture: Impact of tourism on Balinese culture. The research is carried out in Bali, by examining Balinese and their relationship with international tourists. Bali selected because the locus of the interaction occurs on the island. The research found that tourism has made Balinese culture more creative but at the same time it is destructive. Tourism has degrading the value of Balinese culture, but economically benefits local people. Acculturation has created something new, adaptation and alteration and creating traditional and touristic world. Acculturation has made Balinese touristic culture evolved and rich. Both Balinese and tourists found that tourism endangers Balinese environments, but it also creates awareness of preservation. Tourism economically beneficial, but the role and participation of Balinese is on the employees level not business owner. A conclusion could be drown that tradition of acculturation continued in tourism, it has made Balinese culture known and exposed to tourists for foreign exchange. But over exposition has created conflict between religious and touristic world. Balinese culture exposition has economically benefited Balinese people, but proportion of business ownership is very low, and the income distribution for Balinese is very small. Environmentally tourism has created some adverse problem, but the awareness of the role of the environment in tourism increases that encourage them to preserve it. Balinese culture Exposition to tourism has attracted millions of tourists to the island, but Balinese access in the ownership of tourism enterprises is very limited. The implication is that community based rural tourism has to be encouraged to give Balinese as stake holders a fair income distribution from tourism. Rural traditional institution has to be empowered to promote their culture to support tourism and tourists should not merely welcomed as consumers but partners to sustain tourism in Bali, and disseminate to tourists that Balinese has a religious world and has to be respected